STUDY OF SAFETY INDICATORS OF THE CEREAL PRODUCT “CEREAL BAR” - T. Y. Gumerov; A. R. Usmanova; Z. S. Mingaleeva; E. Y. Tarasova (Пищевые системы, 2022)
The study of food products is the most important method for creating proves of their food safety based on generally accepted scientific ideas and current international and national legal norms of food safety. At the stage of laboratory research it is possible to objectively prove the efficiency and safety of new types of food products while their consumption according to certain health indications among the relevant group of people, including staff working in hazardous industrial environment. In the Russian Federation the procedure for assessing the safety and running the laboratory tests of food products are regulated by the Federal Laws on the Quality and Safety of Food Products, regulations on provision of public catering services, methodological recommendations for assessing the risk to public health in case of exposure to microbial factors contained in food products, as well as technical regulations of the Customs Union on food safety. The authors have developed regulatory and technical documentation for the cereal product “Cereal bar” and presented data on its safety when consumed. Conclusions about the product are made on the basis of a study of its chronic toxicity. It has been established that the ingredients composition of the cereal bar, included in the diet of laboratory animals, provided a positive effect on their body condition, weight gain and did not cause abnormal changes in the volume of internal organs and the development of pathologies that could indicate a side effect of the product. During study of the hematological and biochemical parameters, no significant differences were found between the data of the control group and experimental group of the animals. The conducted studies of the cereal product “Cereal bar” confirm the absence of a potential risk of developing chronic toxicity in case of introduction of the cereal bar to the animals’ diets and its consumption over a long period of time.